Unaccustomed high mileage compared to intensity training-related neuromuscular excitability in distance runners - Lehmann, M.; Jakob, E.; Gastmann, U.; Steinacker, J. M.; Keul, J. (European Journal of Applied Physiology, 1995)
The influence of a 4-week unaccustomed average 103% mileage increase (ITV, increase in training volume; n = 8; average baseline mileage 85.9 km.week-1, final mileage 174.6 km.week-1) on performance and neuromuscular excitability (NME) was tested in experienced distance runners and controlled 1 year later by a 4-week unaccustomed average 152% increase in tempo-pace and interval-runs (ITI, increase in training intensity; n = 9; baseline 9 km.week-1 final 22.7 km.week-1) with an average total mileage of 61.7 km.week-1 (week 1) to 84.7 km.week-1 (week 4). Seven athletes participated in ITV as (week 4). Seven athletes participated in ITV as well as in ITI. During incremental treadmill test performance at a lactate concentration of 2 mmol.1-1 (2 LP) increased, and at 4 mmol.1-1 (4 LP) performance did not change, whereas total running distance (TD) during the incremental test decreased in ITV compared to an increase in 2 LP, 4 LP and TD during ITI which may indicate that there was an ITV-related overtraining. The NME of the reference muscles vastus medialis and rectus femoris deteriorated in ITV (day 28 compared to 0) compared to constant values during ITI, reflecting an ITV-related overload of neuromuscular structures.